Identificar los peligros y evaluar los riesgos en las instalaciones de la empresa Granja Fundo Don Jorge San Juan Bautista - Huanca Diaz, Jose Ricardo (2023)
In the farm fundo don Jorge, located on the zungarococha-quebrada shushuna road, the study was made to measure the types of dangers, their level of risk and significance that each of them have, it was determined that the most frequent types of dangers in the different productive chains are mostly dangers: of the working or locative environment having as main dangers: the poor condition of the access roads, the conditions of the sheds, the deteriorated infrastructure of the corrals; there are also ergonomic hazards because workers are not more careful when moving loads and finally biological hazards although on a smaller scale, the same ones that have a moderate level of risk. The production chain that presents hazards with a high level of significant risk to workers is located in the mill area, having among the main risks to suffer burns, electrocutation, and hand entrapment by moving machines. This is because this company does not allocate a budget to address safety and health issues, likewise the workers do not have training for the position they hold or are trained in occupational safety issues.